Attitudes of ICU and Oncology Nurses towards Euthanasia - neda asadi; Zahra Royani; mohammad heidari; mansureh ghodusi borujeni (Zanjan University of Medical Sciences and Health Services, 2014)
Background and Objectives: Since nurses have an important role in caring for end-stage patients, their attitudes toward euthanasia is important to be considered. This study aimed to examine the attitudes of nurses who work in the ICUs and oncology wards towards euthanasia. Materials and Methods: In this cross-sectional study, 205 nurses working in oncology wards and ICUs in teaching hospitals of Kerman University of Medical Sciences were enrolled during June to November 2012. Data were gathered using the Euthanasia Attitude Scale (EAS) and demographic information list. The data were analyzed using the statistical methods in the SPSS version 16. Results: The mean score of the nurseschr('39') attitudes towards euthanasia was 58.51±14.19. The majority of nurses (n=163 79.5%) received a score less than 75, and were opposed to euthanasia. The regression analysis showed that one year of age increase made the attitude more negative (p<0.025). The attitude of nurses with more than 5 years of work experiences was 15.05 more negative than the nurses with work experiences less than 5 years (p>0.003). Conclusion: The results of this study showed that most nurses had negative views on euthanasia. It seems that further studies should be conducted to clarify determinants of the nurses' attitudes and their roles in management of end-stage patients.